2024
DOI: 10.1186/s12964-023-01462-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcending frontiers in prostate cancer: the role of oncometabolites on epigenetic regulation, CSCs, and tumor microenvironment to identify new therapeutic strategies

Giulia Ambrosini,
Marco Cordani,
Ali Zarrabi
et al.

Abstract: Prostate cancer, as one of the most prevalent malignancies in males, exhibits an approximate 5-year survival rate of 95% in advanced stages. A myriad of molecular events and mutations, including the accumulation of oncometabolites, underpin the genesis and progression of this cancer type. Despite growing research demonstrating the pivotal role of oncometabolites in supporting various cancers, including prostate cancer, the root causes of their accumulation, especially in the absence of enzymatic mutations, rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 208 publications
0
1
0
Order By: Relevance
“…These oncometabolites, extending their influence beyond their cells of origin, significantly impact the TME, thereby promoting processes such as tumor invasion, metastasis, and migration ( Figure 2 ). Numerous studies have demonstrated that oncometabolites can alter cellular processes and communication, leading to notable changes in gene expression, signal transduction, and overall cellular behavior, thereby playing a crucial role in cancer progression [ 35 , 36 ]. This highlights that the influence of mutp53 on metabolic pathways might drive cancer progression through the accumulation of oncometabolites, which exert a range of oncogenic effects.…”
Section: Novel Mechanisms Of Mutant P53 Gain Of Function (Gof)mentioning
confidence: 99%
“…These oncometabolites, extending their influence beyond their cells of origin, significantly impact the TME, thereby promoting processes such as tumor invasion, metastasis, and migration ( Figure 2 ). Numerous studies have demonstrated that oncometabolites can alter cellular processes and communication, leading to notable changes in gene expression, signal transduction, and overall cellular behavior, thereby playing a crucial role in cancer progression [ 35 , 36 ]. This highlights that the influence of mutp53 on metabolic pathways might drive cancer progression through the accumulation of oncometabolites, which exert a range of oncogenic effects.…”
Section: Novel Mechanisms Of Mutant P53 Gain Of Function (Gof)mentioning
confidence: 99%
“…The expression of these molecules increases concomitantly with tumor progression and contributes to the promotion of metastasis 22 . The clinical significance of ADSCs in prostate cancer research lies in their ability to modulate the TME and thus influence the viability of tumor cells 23 25 . However, the role of ADSCs in prostate cancer is complex, with opposite evidence suggesting both promotional and inhibitory effects on tumor growth 26 28 .…”
Section: Introductionmentioning
confidence: 99%